An Improved DTN Scheme for Large-Scale LEO Satellite Networks. (21st February 2023) - Liu, Gaosai; Jiang, Xinglong; Li, Huawang; Sun, Siyue; Zhang, Zhenhua; Liang, Guang
Abstract : A large-scale low Earth orbit (LEO) satellite network has the characteristics of a complex link environment, a large number of satellites, and the limited resources of a single satellite. Applying traditional routing algorithms has disadvantages such as high overhead, high end-to-end latency, and low message delivery rate. This paper proposes an improved delay tolerant (DTN) scheme for large-scale LEO satellite networks (LIDTN) to improve transmission efficiency and reduce the resource overhead and end-to-end latency of large-scale satellite networks. This scheme improves the network performance in three aspects: next hop selection, congestion control mechanism, and acknowledgment mechanism. For the next hop selection, we propose an equivalent distance and priori knowledge-based forwarding strategy (EPFS), which has the advantages of low overhead, loop avoidance, and fast convergence. For congestion control, we put forward an emergency function-based bundle drop algorithm (EBDA). For acknowledging, we propose the virtual acknowledgment algorithm (VAA) by combining the characteristics of many path hops and high link disruption rates in large-scale constellations. Finally, we simulate and verify the LIDTN scheme on the OneWeb constellation. The results show that the LIDTN scheme is suitable for large-scale constellations, the EPFS algorithm can reduce the network overhead during data transmission, EBDA can reduce the bundle drop rate, and VAA can reduce the end-to-end latency. LIDTN provides a new solution for large-scale constellation communication.